Sosialisasi Pajak, Tingkat Pendidikan dan Sanksi Pajak terkait dengan Kepatuhan Wajib Pajak UKM - Narti Eka Putri; Nurhasanah Nurhasanah (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2019)
This study aims to examine the effect of tax socialization, education level and tax sanctions on SME entrepreneurs. Respondents from this study were SME entrepreneurs in the East Manggar Belitung area as many as 353 people. This study uses a quantitative method in which the determination of the sample uses a purposive sampling method. The data used is primary data collected through a questionnaire. This research uses multiple regression analysis for hypothesis testing and instrument testing is analyzed using validity and reliability tests. The results of this study prove that tax socialization, tax sanctions partially have a positive and significant effect on SME taxpayer compliance. Meanwhile, the level of education is not significant to the compliance of SME taxpayers in East Manggar Belitung.